Do Different Groups Have Different Epistemic Intuitions? A Reply to Jennifer Nagel Do Different Groups Have Different Epistemic Intuitions? A Reply to Jennifer Nagel. - Stich, Stephen (Philosophy & Phenomenological Research, 2013)
The author offers his views on the annotations of author Jennifer Nagel regarding the different epistemic intuitions of different groups. He mentions that intuitions play a crucial function in modern epistomology. He reflects on the misleading theoretical and experimental arguments implemented by Nagel regarding epistemic intuitions. The author also aims to correct the errors by distinguishing different epistemological projects in which intuitions are taken to be evidence.